Pendidikan Karakter Berwawasan Kearifan Lokal melalui Warisan Budaya Berbenda di Kabupaten Jepara - Efa Ida Amaliyah; Ulfah Rahmawati; Khoirunnisaa' Khoirunnisaa' (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2025)
Globalization changes morality and human thought patterns in the world of education. Students experience a shift in behavior towards ancestral culture. This study looks at students' attention to recognize cultural heritage objects in the midst of the onslaught of the era of fast information through social media. This research uses an anthropological approach to education, through observation, interviews, and documentation studies by looking at the decline in character education found in various cases in society. This research shows that cultural heritage objects in Jepara, Mantingan Mosque and Kartini Museum have values as local wisdom of Jepara as a form of character education for the younger generation. Mantingan Mosque is the center of Islamic civilization in Jepara from the beginning of its establishment until now, among others as a place to deepen the teachings of Islam and learn history. The history of the Mantingan Mosque shows that Islam has interacted with the culture that existed before Islam entered Jepara, namely China. The birth of the Kartini Museum is a form of respect for RA. Kartini. The story of RA. Kartini that can be seen from these historical objects have values or meanings for the current generation.